KINERJA KEUANGAN KANTOR PELAYANANAN PERBENDAHARAAN NEGARA SAMARINDA - Sunoto, M Arif (EKONOMIA, 2012)
We need a certain benchmark or standard to assess financial performance of working unit. Standards can be either historical comparison or financial data comparison in a period or between two sequential periods. Without such comparison, we can’t know whether working unit’s performance is increasing or decreasing.   This research was conducted by making comparison between balance sheet and budget realization data of 2010 and 2011 and analyzing performance measurement of 2011 in KPPN Samarinda as working unit. This research used analytical technique to compare financial changes between same item on financial statement in two sequential period and percentage analysis technique to compare an item with the total in a financial statement.The conclusion of the research is growth of assets, liabilities and fund equity, revenue and expenditure realization, implementation aspect and benefit aspect affect financial performance improvement of KPPN Samarinda as working unit from 2010 to 2011. This research also showed that KPPN Samarinda have an excellent value in performance measurement in 2011.